Effect of R-values changes in the baseline codes: Embodied energy and environmental life cycle impacts of building envelopes - Ayman M. Raouf; Sami G. Al-Ghamdi (Energy Reports, 2020)
The major environmental and economic burdens occurring from the high-energy consumption of buildings led to energy performance being a critical aspect for green building rating systems. Building energy codes play an important role for such performances through establishing the baseline requirements to meet the rating system needs. Building information modeling (BIM) was used to model a concrete masonry unit (CMU) block wall with various insulation thicknesses assigned various insulation layer thicknesses depending on the insulation material property. Multiple scenarios were created in compliance with several energy codes and its different versions. The scenarios modeled were then analyzed using Life Cycle Assessment (LCA) to calibrate environmental performance of different energy codes used as baseline codes for different green building rating systems. The results indicate the differences between the various green building rating systems according to respective energy baseline codes and their versions adopted. Tendencies towards more efficient with less environmentally harmful buildings were observed. Comparing the different codes with the direct impact on the green building rating systems shows that rapid development in energy codes surpassed the impact resulted from adopting the green building rating systems. The amount of reduction in environmental impact was significantly and tangible due to change in the energy code.
Keywords: 330; Life cycle assessment; ASHRAE; Building envelope; Energy; Green buildings; LEED; R-values